Comparison of the Antioxidant Activity of the Different Betula pendula Roth. Extracts from Northern Kazakhstan - Dehaen2, Talgat S. Seitembetov1,3, Amankul J. Seitembetova3, Anastassiya A. Mashentseva1*, Wim (Journal of Phytology, 2011)
The in vitro and in vivo antioxidant activities of ethanolic extracts of the vegetative organs of Betula pendula Roth. were studied by evaluating the ability to scavenge theÃ‚Â  DPPH radical, ABTS cation radical or hydrogen peroxide or by the metal chelation activity or reducing power. The phospholipid oxidation processes were studied using the acute hypoxia model. The changing proportion between acid and neutral phospholipids was used for the estimation of the influence of the birch extract on brain tissue. As an index of the pathological state the information entropy parameters were calculated. It has been found that the rats which had experienced ischemia have a decreased amount of acid PL in the homogenates. Preventive injection of birch extracts brings about normalization of PL level. This fact points out a possibility of applying extracts of Betula Pendula Roth in order to regulate the PL level of experimental rats as well as an estimation of the antioxidant effect of exogenous substances. Key words: Betula vegetative organs, Antioxidant activity, Lipid peroxidation, Phosholipids <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Mashentseva et al. Comparison of the Antioxidant Activity of the Different Betula pendula Roth. Extracts from Northern Kazakhstan. J Phytol 3/1 (2011) 18-25.